Exploring The Islamic Education Practices Among Muslim Students - Farhatun Khalidah binti Zulkanai; Halim bin Ismail; Noor Azizi bin Ismail; Mohd Aderi Che Noh (International Journal of Learning and Education, 2026)
This study was conducted to identify the practise of Islamic education among Muslim students in Sekolah Jenis Kebangsaan Cina (SJKC) and to determine the most attractive topic among them. This study also aimed to explore the factors that influenced the practise of Islamic education among Muslim students in SJKC. The quantitative techniques were used in this study through the use of a questionnaire instrument, which was then analysed using the SPSS version.The study found that syahadah is the most commonly practised component among Muslim students at SJKC. The study also reveals that the Sirah is the most popular topic and the Islamic education teacher’s encouragement is the main factor that influences the practise of Muslim students on the subject of Islamic education in SJKC. This study has an impact on Islamic Education teachers and students and raises awareness of the value of Islamic Education subjects.Keywords: Islamic Education Practices, Islamic Education Teacher’s, Muslim Students.